2019
DOI: 10.1016/j.hpb.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic pancreatoduodenectomy with open or laparoscopic reconstruction during the learning curve: a multicenter propensity score matched study

Abstract: Background: Laparoscopic pancreatoduodenectomy with open reconstruction (LPD-OR) has been suggested to lower the rate of postoperative pancreatic fistula reported after laparoscopic pancreatoduodenectomy with laparoscopic reconstruction (LPD). Propensity score matched studies are, lacking. Methods: This is a multicenter prospective cohort study including patients from 7 Dutch centers between 2014-2018. Patients undergoing LPD-OR were matched LPD patients in a 1:1 ratio based on propensity scores. Main outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
3
12
1
Order By: Relevance
“…15 However, this study precluded randomised controlled trials 10,11 and several other important cohort studies, limiting validity of their review. [16][17][18][19][20] Hence, this systematic review aims to comprehensively evaluate all current and relevant evidence and perform a network meta-analysis to identify techniques associated with superior peri-operative outcomes in patients undergoing PD using a similar methodology to a recent publication on distal pancreatectomy. 21 In order to include a broader spectrum of surgical approaches, this review will summarise findings of both randomised and non-randomised studies.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, this study precluded randomised controlled trials 10,11 and several other important cohort studies, limiting validity of their review. [16][17][18][19][20] Hence, this systematic review aims to comprehensively evaluate all current and relevant evidence and perform a network meta-analysis to identify techniques associated with superior peri-operative outcomes in patients undergoing PD using a similar methodology to a recent publication on distal pancreatectomy. 21 In order to include a broader spectrum of surgical approaches, this review will summarise findings of both randomised and non-randomised studies.…”
Section: Introductionmentioning
confidence: 99%
“…The initial part of the learning curve associates with higher rate of complications [17]. Recent multicenter propensity score matched study found that during initial (median = 27 (10-37) cases per center) learning curve, there is no benefit that was found for LPD with open reconstruction (hybrid), as compared to totally laparoscopic PD [48]. More than that, according to LAELAPS-2 multicenter training program in LPD, 27 laparoscopic PD was not enough to overcome very early learning curve (commencement of training), which additionally shows the importance of the present study [49].…”
Section: Discussionmentioning
confidence: 99%
“…Kantor et al analyzed 1277 patients after MIPD (robotic, laparoscopic, robotic-assisted laparoscopic, and robotic or laparoscopic procedures with open assistance and observed a 15% urgent conversion rate, (23.3% for laparoscopic PD and 12.5% for robotic PD) [27]. van Hilst et al reported higher conversion rate for LPD with open reconstruction, and the unplanned conversion rate was 21% versus 9% with LPD (p < 0.001) [48]. This can be explained by the fact that the planned conversion is original part of preoperative planning.…”
Section: Discussionmentioning
confidence: 99%
“…
We read article with interest on "Laparoscopic pancreatoduodenectomy with open (LPD-OR) or laparoscopic reconstruction (LPD) during the learning curve: a multicenter propensity score matched study" written by Jony van Hilst colleagues. 1 We congratulate them for on devising this propensity score matched cohort study to compare LPD-OR or LPD.Although much literature has been published about postoperative complications of this morbid procedure, we are yet to find clear answer of how to reduce pancreas related complications. We were happy to see that primary aim of this study was to compare post-operative pancreatic fistula rates (POPF) and complications after pancreatoduodenectomy, whereas in two RCTS, 2,3 hospital stay was the primary outcome measure.Minimally invasive approach has proved to be beneficial to patients in all other gastrointestinal surgical procedures.
…”
mentioning
confidence: 99%
“…We read article with interest on "Laparoscopic pancreatoduodenectomy with open (LPD-OR) or laparoscopic reconstruction (LPD) during the learning curve: a multicenter propensity score matched study" written by Jony van Hilst colleagues. 1 We congratulate them for on devising this propensity score matched cohort study to compare LPD-OR or LPD.…”
mentioning
confidence: 99%